Pan European R&D a perspective. - Peterson, J. (IEEE spectrum)
New goals for Europe-wide technology policy are emerging, perhaps rather late in the day. In the early 1980s, Europe's leadership was seeking ways to help its large electronics producers hold their own against stiff US and Japanese competition. Now, nearly two decades later, many European companies still lack a competitive edge, and worry about unemployment has deepened. Yet, because of maturing views about the world economy, the focus of the policies of the European Union (EU) has changed. Large companies are seen as fighting for shares of intensely competitive global markets, in which uncertainty and innovation have become a way of life. While retaining a base in their home country, they conduct business around the world. Thus, most multinationals collaborate on the one hand at the regional and local levels, with many firms both large and small, and on the other hand at the global level, with other multinationals. Why, then, adopt technology policies that pay them to collaborate in conducting R&D, which they all do anyway. It would seem far more sensible to encourage the diffusion of new technologies and promote the health of smaller, under-capitalized companies. European technology policies have already influenced tendencies in this direction. They have encouraged collaboration among firms and research institutions across the European Community. Thanks to the Brussels-based R&D programs, companies have learned to work with firms beyond their national borders as a matter of routine, to seek new opportunities beyond their traditional home markets, and generally to think in European terms